2021
DOI: 10.1177/1464420721990413
|View full text |Cite
|
Sign up to set email alerts
|

Drilling performance of uncoated brad spur tools for high-strength carbon fiber-reinforced polymer laminates

Abstract: High-strength carbon fiber-reinforced polymers have been a promising alternative to conventional fibrous composites because of their extremely high properties. Mechanical drilling is a necessary operation to create boreholes for riveting and bolting different composite structures into assemblies. However, the high-strength carbon fiber-reinforced polymers pose much more serious machining issues than the conventional ones. The present work aims to investigate the drilling performance of one type of uncoated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As expected, the quality of the holes gets worse as the number of drills increases. It should be noted that the wear of the tools can affect surface quality, delamination and thrust forces as found by Lin et al 28 This trend is noticeable for the surface roughness, diameter deviation and delamination. Nevertheless, the trend depends on the configuration.…”
Section: Resultsmentioning
confidence: 60%
“…As expected, the quality of the holes gets worse as the number of drills increases. It should be noted that the wear of the tools can affect surface quality, delamination and thrust forces as found by Lin et al 28 This trend is noticeable for the surface roughness, diameter deviation and delamination. Nevertheless, the trend depends on the configuration.…”
Section: Resultsmentioning
confidence: 60%
“…Karalis, G [6] studied the dynamic behavior and failure mechanism of laminates under underwater tensile loads. Lin et al [7] conducted a comparative analysis of the dynamic failure behavior of flat and curved panel structures of woven basalt/epoxy laminates under blast loading, emphasizing the important influence of structural curvature on the dynamic response. Wei et al [8] carried out experiments and numerical simulations on the high-speed penetration of laminates and concluded that, in addition to fiber failure, laminates under penetration loads also include spalling and matrix cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Several drill tool geometries have been used in drilling the stacks and in the evaluation of critical thrust force and torque. [17][18] Palanikumar et al, have assessed the effect of various parameters affecting the surface roughness of the drilled hole of GFRP composites through experimental design. 19 Simulated annealing techniques have been adopted by Basavarajappa et al, to study the effects of machining parameters on the delamination factor, specific cutting coefficient, and surface roughness of the drilled hole.…”
Section: Introductionmentioning
confidence: 99%